Impact of Rotational Speed and Impeller Types on Flow Patterns and Mixing Time in a Side-Entry Dual Mixer: A Study Using CFD and Visual Methods - Ardista Izdhihar Kaloka; Shendi Haris Firmansyah; Marsyada Maghfirotul Wafiroh; Ni’mah Wati; Icha Nur Prayadi; Danawati Hari Prajitno (IPTEK The Journal of Engineering, 2026)
The effectiveness of industrial mixing processes is strongly influenced by impeller type and rotational speed because these parameters determine flow pattern, turbulence intensity, and fluid homogeneity. This study analyzes the effect of impeller type and rotational speed on flow pattern, mixing time, and turbulence characteristics in a side-entry dual mixer using a calcium carbonate (CaCO₃) suspension and water. The analysis was conducted using computational fluid dynamics (CFD) modeling and visual observation to identify circulation patterns and stagnant zones. Three impeller configurations were evaluated: dual four-blade propellers, four-blade pitched blade turbines (4-PBT), and a combination of both, operated at 300 and 600 rpm. The results show that impeller type significantly influences the flow pattern, while increasing rotational speed reduces mixing time. The dual 4-PBT at 600 rpm provided the best performance, characterized by multiple axial–radial circulation loops without stagnant zones and the fastest mixing time of 120 s. This configuration also produced the highest Reynolds number of 3127.19, indicating a transitional flow regime that enhances turbulence and accelerates homogenization. These results demonstrate the importance of selecting appropriate impeller types and rotational speeds to improve industrial mixing efficiency.